The business of rankings - Abd Razak, Dzulkifli (2010)
THE rankings game is here again. This time it involves two types of rankings that allow us to understand what the game is all about from different perspectives. Firstly, it is hardly surprising that United States' Harvard University once again — for the eighth consecutive year — topped a recent world universities rankings published by Shanghai Jaiotong University. The results of the rankings are sharply criticised in Europe as the list is dominated by American institutions with the University of California, Berkeley being second, followed by Stanford University.